Artmaking in Elementary School Art Therapy: Associations with Pre-Treatment Behavioral Problems and Therapy Outcomes - Sharon Snir (Children, 2022)
Engaging in artmaking is one of the key components of art therapy. Theoretical conceptualizations posit that artmaking is not only influenced by the mental state of the artmaker, but can also modify it. The quantitative longitudinal study reported here examined these assumptions in the context of school art therapy. Seventy-seven elementary school students in art therapy in Israel completed the Art Based Intervention Questionnaire (ABI) three times during the therapy year. Their parents and homeroom teachers reported on the students’ behavioral and emotional problems on the Child Behavior Checklist (CBCL for parents, and TRF version for teachers). The results indicated an inverse correlation between the students’ externalizing and mixed problems before starting treatment and these clients’ experiences of artmaking during the first month of therapy. A regression model for predicting gain scores on the TRF internalizing problem indices was significant, whereas the significant regression predictor was the students’ experience of artmaking at T1. These findings provide initial support for an association between the experience of artmaking and mental state, and an improvement in mental state, and are discussed in relation to the context of school art therapy.